Incidence of self poisoning in patients prescribed psychotropic drugs. - Skegg, K; Skegg, D; Richards, S (1983)
The drugs most commonly used in self poisoning are the psychotropics, but the proportion of patients given these drugs who take overdoses is unknown. In a prospective study of 43117 people in Oxfordshire, prescriptions issued by general practitioners were linked with records of hospital admissions and deaths. During two years there were 79 episodes of deliberate self poisoning leading to hospital admission or death. The number of patients who took overdoses of psychotropic drugs was small in relation to the total number prescribed such drugs. Of 5600 people aged 10 or older who received psychotropic drugs during one year, 17 (3.0 per 1000) poisoned themselves with these drugs within 12 months. The rate of self poisoning with psychotropic drugs declined significantly with increasing age (p less than 0.001). Almost three quarters of the patients who took overdoses of prescribed psychotropics received further psychotropic drugs during the three months after their admission to hospital.